2017
DOI: 10.1002/psc.3058
|View full text |Cite
|
Sign up to set email alerts
|

Design and study of lipopeptide inhibitors on preventing aggregation of human islet amyloid polypeptide residues 11‐20

Abstract: Type 2 diabetes mellitus, a kind of conformational disease, has become an epidemic disease, which seriously endangers the quality of life and health of human beings. The deposition of human islet amyloid polypeptide (hIAPP) has been considered as one of the major pathological features of type 2 diabetes mellitus. As lipopeptides have some hydrophobic groups, which are similar to the reported aggregation inhibitors, and some lipopeptides could prevent cells from depositing of amyloid fibrils, several potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(207 reference statements)
0
6
0
Order By: Relevance
“…In a later report, the effect of macrocyclic β-sheet peptides on the relative populations of the two fibril polymorphs of hIAPP was evaluated. 82 Recently 84 The ThT assay depicted a progressive increase in the anti-aggregation ability of lipopeptide inhibitors against hIAPP (11−20) aggregation on increasing the length of alkyl chain, which indicated a significant contribution of the hydrophobicity of lipopeptides to the inhibitory effect of lipopeptides. The results revealed that increasing the number of arginine residues did not led to a higher inhibitory effect of lipopeptides.…”
Section: Peptide Inhibitors Of Hiapp Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a later report, the effect of macrocyclic β-sheet peptides on the relative populations of the two fibril polymorphs of hIAPP was evaluated. 82 Recently 84 The ThT assay depicted a progressive increase in the anti-aggregation ability of lipopeptide inhibitors against hIAPP (11−20) aggregation on increasing the length of alkyl chain, which indicated a significant contribution of the hydrophobicity of lipopeptides to the inhibitory effect of lipopeptides. The results revealed that increasing the number of arginine residues did not led to a higher inhibitory effect of lipopeptides.…”
Section: Peptide Inhibitors Of Hiapp Aggregationmentioning
confidence: 99%
“…In 2017, Mao et al engineered and synthesized several potential lipopeptide inhibitors C x -RRRR-NH 2 ( x = 4, 6, 8, 10, 12, and 14) and C14-R n -NH 2 ( n = 2, 3, 4 and 5) against hIAPP (11–20) aggregation . The ThT assay depicted a progressive increase in the anti-aggregation ability of lipopeptide inhibitors against hIAPP (11–20) aggregation on increasing the length of alkyl chain, which indicated a significant contribution of the hydrophobicity of lipopeptides to the inhibitory effect of lipopeptides.…”
Section: Peptide Inhibitors Of Hiapp Aggregationmentioning
confidence: 99%
“…However, during the second phase of clinical trials, davalintide showed no better effects than pramlintide; hence, the development of the former drug was discontinued [ 161 ]. Table S2 [ 156 , 159 , [162] , [163] , [164] , [165] , [166] , [167] , [168] , [169] , [170] , [171] , [172] , [173] , [174] , [175] , [176] , [177] , [178] , [179] , [180] , [181] , [182] , [183] , [184] , [185] , [186] , [187] , [188] , [189] , [190] , [191] , [192] , [193] , [194] , [195] , [196] , [197] , [198] ] presents some other peptide inhibitors designed and evaluated for their potential against hIAPP aggregation, for example, inhibitors derived from an internal sequence of hIAPP; those containing natural amino acids [ 162 , 169 ], d -amino acids [ 170 ], or non-natural amino acids [ 175 , 182 ]; and N -alkylated [ 186 ], cyclic [ 189 , 190 ], and conjugated [ 188 ] peptide inhibitors. In 2009, Potter et al.…”
Section: Hiapp As a Drug Targetmentioning
confidence: 99%
“…N-Terminal fatty acid acylation of short peptides has been shown to increase their efficacy, stability, and cell permeability in a variety of applications. [ 8 ] Kim and coworkers, for example, reported that the palmitoylation of a heptamer discovered in a screen for proliferation PPI modulators produced inhibitors with excellent activity in vitro and in cells. [ 8d ] We hypothesized that such a strategy could produce more potent peptide inhibitors of activator–coactivator PPIs.…”
mentioning
confidence: 99%